2021
DOI: 10.6065/apem.2040132.066
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and its contributing factors in primary school-aged children in Indonesia, a sun-rich country

Abstract: Vitamin D insufficiency and its contributing factors in primary school-aged children inIndonesia, a sun-rich country Running title: Vitamin D insufficiency in primary school-aged children in Indonesia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 28 publications
3
36
0
2
Order By: Relevance
“…To date, observation of vitamin D concentration in the Indonesian population was focusing on the population at risks such as children, adolescents, and pregnant women [17][18][19]. Although observation of vitamin D concentration in postmenopausal breast cancer patients has been done previously in Surabaya, Indonesia [20], the association between vitamin D level and breast cancer characteristics remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…To date, observation of vitamin D concentration in the Indonesian population was focusing on the population at risks such as children, adolescents, and pregnant women [17][18][19]. Although observation of vitamin D concentration in postmenopausal breast cancer patients has been done previously in Surabaya, Indonesia [20], the association between vitamin D level and breast cancer characteristics remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The most common reported risk factors for VDD in the region were female sex,25 27 33 34 37 39 40 42 44 45 49 50 older children,22 27 31 37 40 49 51 urban living,27 37 38 44 51 52 covered-up clothing for religious purposes,37 39 53 exposure to sunlight <30 min/day35 39 40 54 and obesity31 37 42 44 45 (table 1). Subgroup analysis by gender and residence are presented in figure 5 and online supplemental file 5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the difference in the amount of sunlight exposure by sex is another possible reason. Pulungan et al [ 24 ] reported that sun exposure duration was a major cause of vitamin D deficiency in children. Tsugawa et al [ 25 ] reported that the serum 25(OH)D level was lower in girls than in boys during puberty, which might have been attributed to a greater amount of outdoor exercise in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%